The Countermovement Jump Mechanics of Mixed Martial Arts Competitors. Issue 4 (April 2020) - James, Lachlan P.; Connick, Mark; Haff, G. Gregory; Kelly, Vincent G.; Beckman, Emma M.
Abstract : Abstract: James, LP, Connick, M, Haff, GG, Kelly, VG, and Beckman, EM. The countermovement jump mechanics of mixed martial arts competitors. J Strength Cond Res 34(4): 982–987, 2020—Gross countermovement jump (CMJ) performance measures are greater in higher-level mixed martial arts (MMA) competitors than lower-level (LL) competitors. Differences in CMJ kinetics and kinematics throughout the action may explain those CMJ performance differences, but this remains to be investigated. After warm-up and familiarization, 27 MMA competitors (divided into 2 groups based on competitive standard; higher level [HL]: n = 14 and LL: n = 13) completed 3 maximal effort CMJs. Power, force, velocity, displacement-time waveforms and eccentric phase displacement, eccentric time, eccentric impulse, and the modified reactive strength index (RSImod) were compared between groups using statistical parametric mapping procedures and independent t -tests. Power (between 65 and 71% of the power-time curve) was greater in the HL than that of the LL group ( p = 0.01) despite no differences in eccentric displacement ( p = 0.50) or movement time ( p = 0.17) between groups. The HL group demonstrated a greater RSImod ( p = 0.05) alongside a reduced eccentric time ( p = 0.02) and eccentric impulse ( p = 0.02). These findings suggest that timing and control of lower-body force production contributed to between-group differences in CMJ performance among MMA competitors.